ANALISIS PEMBELAJARAN KOOPERATIF MELALUI MODEL THINK PAIR SHARE (TPS) DALAM MENCAPAI HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Uus Toharudin (Jurnal Soshum Insentif, 2020)
Abstract – Still the low subjects of Science Sciences Elementary School grade IV students became an issue for teaching teachers in schools. IPA Science is an important student eye in improving the way constructive thinking students in responding to the development of the world and the universe. Research objectives to increase student learning activities as per expectations and target goals set by the school. Research methods using quasi experiments are descriptive survey, field study, Instrutemen, and literature study. The results showed significant differences in student creative thinking skills and class teachers after using the Think-Pair-Share (TPS) Cooperative learning model for SCIENCE subjects for elementary school grade IV students. Abstrak – Masih rendahnya mata pelajaran sains IPA siswa kelas IV SD menjadi persoalan bagi guru ajar di sekolah. Sains IPA adalah mata pelajar penting dalam meningkatkan cara berpikir konstruktif siswa dalam merespon perkembangan ilmu pengetahuan alam semesta. Tujuan penelitian untuk meningkatkan aktivitas belajar siswa sesuai harapan dan sasaran target yang ditetapkan sekolah. Metode penelitian menggunakan quasi eksperimen bersifat descriptive survey, field study, instrutemen, dan studi literature. Hasil penelitian menunjukan terdapat perbedaan signifikan kemampuan berpikir siswa dan guru kelas setelah menggunakan model pembelajaran kooperatif Think-Pair-Share (TPS) untuk mata pelajaran IPA bagi siswa kelas IV Sekolah Dasar.